Domestic Credit and Stock Market Impact on Economic Growth: A New Evidence in Five ASEAN Countries - Tuti Eka Asmarani; Endah Ayu Ningsih (Bina Nusantara University, 2022)
Capital accumulation and technological innovation had been the two channels through which the financial sector plays a vital role in the growth of economy. However, there are some different results between banking and stock market. The research tested the Solow-Swan growth model augmented with financial markets to show that domestic credit markets and equity from stock markets are two long run determinants of Gross Domestic Products (GDP) per capita in five ASEAN countries: Indonesia, Malaysia, Singapore, Thailand, and Philippines. The research used data from 2000 to 2019 tested with panel regression. The result shows that all determinant variables have a positive impact on economic growth. The domestic credit also has a higher impact on the growth of economy than the stock market. In addition, domestic credit and stock market has statistically significant positif impact to economic growth across five ASEAN countries. The researchalso finds that although population in five ASEAN countries give positive effect to economic growth, it is statistically not convincing. It is suggested that people in ASEAN have already used technology, so population augmented encourages economic growth.